THE IMPORTANCE OF LEARNING ENGLISH IN THE MODERN WORLD - Isroilova Gulruh (TADQIQOTLAR, 2026)
Abstract. In the modern globalized world, the English language plays a crucial role as a primary means of international communication. It is widely used in education, science, business, technology, and diplomacy, making it an essential skill for individuals seeking academic and professional success. Learning English enables people to access a vast amount of information, participate in global discussions, and build cross-cultural connections. Moreover, proficiency in English enhances career opportunities, promotes cultural exchange, and supports personal development. As digitalization and globalization continue to expand, the importance of learning English becomes increasingly significant, positioning it as a key tool for integration into the modern world.